MODL-28. DEVELOPING A STRATEGY FOR MODELING HIGH-GRADE GLIOMA IN GӦTTINGEN MINIPIGS. (14th November 2022) - Tora, Muhibullah S; Lei, Kecheng; Nagarajan, Purva P; Bray, David P; Rindler, Rima S; Neill, Stewart G; Zhang, Michelle; Texakalidis, Pavlos; Krasnopeyev, Andrey; Gergye, Crystal; James, Raphael; Oshinski, John N; et al.
Abstract: BACKGROUND: The current literature does not describe a reproducible large animal model of intracranial high-grade glioma (HGG). Prior work has demonstrated the feasibility of inducing HGG de-novo in rodents by targeting specific oncogenic pathways. Here we report our approach to the production of supratentorial HGG in a series of minipigs through lentiviral gene transfer and subsequent initial characterization of a porcine glioma cell line. METHODS: Four minipigs received injections into the subcortical white matter using a combination of lentiviral vectors expressing platelet-derived growth factor beta (PDGF-B), HRAS, and shRNA-p53. Animals underwent behavioral monitoring through porcine neurobehavioral scoring (PNS) and veterinary monitoring. Magnetic resonance imaging (MRI) was conducted at endpoint prior to necropsy. Post-mortem tissue biopsies underwent tissue culture and neuropathologic evaluation with hematoxylin and eosin (H&E) staining, immunohistochemistry, and immunofluorescent staining. Data are presented using appropriate statistical tests where relevant and descriptive statistics. RESULTS: Two pigs received 50ul injections and reached endpoint by the end of post-operative week 1 and 2. Two pigs received 25 ul injections and were asymptomatic until a pre-determined endpoint of 4 weeks. MRI scans at endpoint demonstrated contrast enhancing, mass forming lesions at the site of injection with evidence of hemorrhage and perilesional edema, consistent with high-grade glioma. On H&E staining high-grade glioma growth was identified in 100% of animals. We observed immunopositivity for tumor markers GFAP, OLIG2, NG2, SOX2, and PDGFRA, as well as redox markers, and microenvironmental features consistent with high-grade glioma. Porcine glioma cell cultures were found to have significantly greater proliferative rate compared to control, and demonstrated GFAP, OLIG2, PDGFRA, and CD68 immunopositivity. CONCLUSIONS: Lentiviral gene transfer represents a feasible strategy for glioma modeling in the Gӧttingen minipig. With our described methodology, we present a realistic strategy for reproducible modeling of intracranial glioma as a platform for preclinical neurosurgical development programs.